Status of qualitative research in doctoral theses in education in Perú - Nina Condori, Marco (2025)
Introduction: The status of qualitative research in education has been analysed in other countries, while in Peru only isolated data are available. Objective: To analyse the situation of qualitative research in education in Peru. Method: A total of 350 doctoral theses (2004–2024) were reviewed through content analysis and critical analysis of academic discourse. Results: Qualitative studies are comparatively few in contrast to quantitative ones; the qualitative research methods most frequently employed are phenomenology, hermeneutics, and case studies. Furthermore, thesis authors conceive qualitative research as a methodological option different from quantitative research, but this supposed distinction becomes blurred in practice under the precepts of empiricism and positivism. Discussion: By considering qualitative research as exploratory and inductive, and of a less rigorous and subjective nature, it is reduced to a merely technical-instrumental resource.